Development of multi-focus 3D display systems - Kim, S.-K. (IDW '06 - Proceedings of the 13th International Display Workshops, 2006)
Multi-focus 3D display systems are developed and possibility about satisfaction of eye accommodation is tested. The multi-focus means the ability of monocular depth cue to various depth levels. By achieving multi-focus function, we developed a 3D display system for one eye, which can satisfy accommodation to displayed virtual objects within defined depth. The accommodation of one eye is tested and a proof of the satisfaction of the accommodation is given as results by using the proposed 3D display systems.